PEMBUKTIAN SEDERHANA DALAM PERMOHONAN PENUNDAAN KEWAJIBAN PEMBAYARAN UTANG KAJIAN PUTUSAN NOMOR 252/PDT.SUS-PKPU/2021/PN.NIAGA.JKT.PST - Siahaan, Hendri; Achmad Fitrian; Nur Hakim (Bajang Institute, 2024)
In Commercial Court practice, it is included in Decision Number 252/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt.Pst with one of the Legal Considerations that of Article 8 paragraph (4) of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations regarding the existence of debt which are overdue and can be collected and the existence of two or more creditors mutatis mutandis also applies to requests for postponement of debt payment obligations. This is contrary to one of the conditions for submitting a request for a postponement of debt payment obligations by creditors based on Article 222 paragraph (1) of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations and the provisions regarding the Court must grant the submitted request for a temporary postponement of debt payment obligations. by debtors or creditors based on Article 225 paragraph (2) and paragraph (3) of Law Number 37 of 2004 concerning Bankruptcy and Postponement of Debt Payment Obligations. This research uses normative juridical research methods and descriptive analysis based on books, scientific works, journals, articles, decisions and statutory regulations. This research was conducted to analyze simple verification procedures in Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations and simple evidence in requests for postponement of debt payment obligations in the review of Decision Number 252/Pdt.Sus-PKPU/2021/PN.Niaga.Jkt .Pst.